Estudio de factibilidad para la elaboracion artesanal y comercializacion de vino de naranja en la ciudad de Quevedo, año 2013. - Rivera Vera, Karen Lorena (2014)
The research is positioned to help address the need to improve the level of consumption in the Canton Quevedo, leveraging the use of orange produced in the area. Through this study, the orange is vinified with high nutritious. Was assumed as the main objective to carry out a feasibility study for the installation of a production and marketing company that meets all the necessary requirements in terms of technology, economic, environmental and legal. To achieve these objectives was compiled information both primary and secondary levels. In Significantly, much of the search obtained about potential unmet demand for this product was collected directly in the town of Canton Quevedo. In the first chapter of the thesis, the introduction of the research, the problem statement, formulation states, raises the objectives, assumptions are made and the rationale for the project is done. In chapter two the theoretical framework where the most important variables is described and the problems that were the basis for the project is done. Then in chapter three methods, types, techniques of research, the population is determined by detailed research, the sample run that allowed the development of the research is extracted. Then in the fourth chapter develops research through the structure of a feasibility study; where development was analyzed and market research with their projections, technical studio where optimum plant location is determined, the size, XVI engineering among others, economic study where all information is necessary monetary Condeso for implementation of the plant. Finally, conclusions and recommendations on the draft due are highlighted.